Low microsatellite instability: a distinct instability type in gastric cancer? - Kohlruss, Meike; Chakraborty, Shounak; Hapfelmeier, Alexander; Jesinghaus, Moritz; Slotta-Huspenina, Julia; Novotny, Alexander; Peters, Leila; Gaida, Matthias; Ott, Katja; Weichert, Wilko; Pfarr, Nicole; Keller, Gisela (Journal of cancer research and clinical oncology, 2023)
Purpose  We recently showed that low microsatellite instability (MSI-L) is associated with a good response to platinum/5fluorouracil (5-FU) neoadjuvant chemotherapy (CTx) in gastric cancer. The purpose of this study was to characterize the instability pattern and to investigate an association of MSI-L tumors with mutations in genes of DNA repair pathways and with total tumor mutation burden (TMB). - Methods  MSI patterns were compared between 67 MSI high (-H) and 35 MSI-L tumors. Whole-exome sequencing was performed in 34 microsatellite stable (MSS) and 20 MSI-L tumors after or without neoadjuvant CTx. - Results  Of the 35 MSI-L tumors, 33 tumors had instability at a dinucleotide repeat marker. In the homologous recombination (HR) pathway, 10 of the 34 (29%) MSS and 10 of the 20 (50%) MSI-L tumors showed variants (p = 0.154). In the DNA damage tolerance pathway, 6 of the 34 (18%) MSS and 7 of the 20 (35%) MSI-L tumors had variants (p = 0.194). The HR deficiency score was similar in both tumor groups. TMB was significantly higher in MSI-L compared to MSS tumors after CTx (p = 0.046). In the MSS and MSI-L tumors without CTx no difference was observed (p = 1.00). - Conclusion  MSI-L due to instability at dinucleotide repeat markers was associated with increased TMB after neoadjuvant CTx treatment, indicating sensitivity to platinum/5-FU CTx. If confirmed in further studies, this could contribute to refined chemotherapeutic options including immune-based strategies for GC patients with MSI-L tumors.
Gesehen am 18.12.2023